1997
DOI: 10.1076/brhm.28.2.198.12988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superior Cervical Ganglionectomy and Melatonin Replacement on Intra-hypothalamic LHRH Content and Pulsatile Luteinizing Hormone Release in the Mink

Abstract: Long-term effects of subcutaneous melatonin implants on intrahypothalamic LHRH content and on pulsatile luteinizing hormone release have been investigated in ganglionectomized male mink. Animals were submitted to bilateral removal of the superior cervical ganglion in mid-April. A preliminary study revealed that plasma LH concentrations remain at a basal level throughout the year following ganglionectomy. In a second experiment, one month after ganglionectomy and transfer from the natural photoperiod environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…In mink, SCNx or pineal deafferentation following SCGx prevented the stimulation of testicular activity generally induced by autumnal or experimental exposure to short days. These results are consistent with previous results btained in this species (Maurel et al., 1991a, 1992a, 1997). The SCN has been shown to be the major circadian pacemaker generating rhythms and, in mink, SCN destruction affects the general locomotor activity rhythm (Maurel et al., 1991b).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In mink, SCNx or pineal deafferentation following SCGx prevented the stimulation of testicular activity generally induced by autumnal or experimental exposure to short days. These results are consistent with previous results btained in this species (Maurel et al., 1991a, 1992a, 1997). The SCN has been shown to be the major circadian pacemaker generating rhythms and, in mink, SCN destruction affects the general locomotor activity rhythm (Maurel et al., 1991b).…”
Section: Discussionsupporting
confidence: 94%
“…Numerous studies on pinealectomized hamster and sheep have stressed the importance of using a timed infusion paradigm (TIP) for melatonin delivery (reviewed in Bartness et al., 1993), showing the importance of the frequency of signal presentation and of a period of low to zero circulating melatonin concentration. However, it has been shown that the continuous release of melatonin by subcutaneous implants or intrahypothalamic microimplants, without daily rhythmicity may induce gonad stimulation not only at the testicular level but also by reinducing the pulsatile secretion of luteinizing hormone (LH) in various animals including the mink (Maurel et al., 1997). In both sheep and hamster experiments, the duration of the nocturnal melatonin peak and not its circadian phase is most important for determining the reproductive response (see Goldman, 1999).…”
Section: Discussionmentioning
confidence: 99%